The Influence of Macroeconomic Factors to the Dynamics of Stock Exchange in the Republic of Kazakhstan - Niyazbekova, Shakizada Uteulievna; Grekov, Igor Evgenievich; Blokhina, Tatyana Konstantinovna (Economy of Regions, 2016)
This article describes the influence of macroeconomic factors on Kazakhstan Stock Exchange Market by using data from 2005 to 2014. Engle-Granger cointegration test has shown that stock index is cointegrated with the exchange rate, interest rate, CPI and oil price. Vector error correction model has confirmed that macroeconomic variables and the stock index has a long-term equilibrium relationship. Moreover, empirical results have shown that stock index can be used as a leading indicator of the economic situation in Kazakhstan. Therefore, the authors decided to consider the impact of major macroeconomic indicators to the dynamics of the stock market of the Republic of Kazakhstan. The Engle-Granger cointegration test results show that the following variables such as exchange rate, 10-years long-term bond rate, the consumer price index and the Brent oil price are cointegrated with stock index, which means that there is a long-term relationship between this stock market index and these variables. With the help of econometric models, the authors have found the factors such as the exchange rate, the 10-year long-term bonds rate, the consumer price index and the Brent oil price (these factors have the long-term relationship with stock market index). Changes in the dynamics of the stock market index in Kazakhstan are caused by changes in the dynamics of Central bank’s reserves and export. The analysis has shown that the economy of the Republic of Kazakhstan (the index reflects the situation in the real sector of the economy) remains dependent on world oil prices, the volume of exports and the rate of the national currency.